Design of revetec engine cam with cycloidal motion profile - Khairul Anuar, A. Rahman (2012)
Efficiency of conventional engines reduced due to heat and friction losses. Some of the input energy is lost in exhaust gases and water cooling and the mechanical losses due to friction. All conventional engines are using crankshafts to convert the piston reciprocating motion to a rotating motion in the drive line, but crankshafts are responsible of side thrust force, vibrations and also they are not efficient in transferring the power to the drive line. Crank-less and free piston engines were a good example to overcome the crank shaft problems, but these new kinds of engines are facing a control and starting problems. Revetec engine is a new engine arrangement used to increase engine’s efficiency by replacing the crankshaft and the connecting rod used in conventional engines by cams to control the piston movement. In revetec engine, it consists of two counter rotating threelobed cams gearing together. So, both cams contribute of forward motion. Two bearings moving along the profile of both cams (four bearings for all) and stay in contact with the cams at all times. The two cams rotate and raise the piston with a scissor-like action to the bearings. It meaning, in every cycles of the revetec engine there are three power stokes compared to one power stroke in the conventional engines. Based on revetec engine performing, Cam profile contributes great effect in combustion characteristics, so it is very important to find the suitable cam profile to achieve the maximum cylinder pressure. In this project a computational work. Based on comparison result of the project between conventional engine and revetec engine. The result obtained from this study has shown that by using a cam profile, with which Cycloidal motion was applied to the piston, the cylinder pressure can be increased up to 23.91 percent.